Nitrogen fertilization differentially affects the symbiotic capacity of two co‐occurring ectomycorrhizal species. (12th January 2022) - Plett, Krista L.; Snijders, Fridtjof; Castañeda‐Gómez, Laura; Wong‐Bajracharya, Johanna W.‐H.; Anderson, Ian C.; Carrillo, Yolima; Plett, Jonathan M.
Summary: Forest trees rely on ectomycorrhizal (ECM) fungi to obtain growth‐limiting nutrients. While addition of nitrogen (N) has the potential to disrupt these critical relationships, there is conflicting evidence as to the mechanism by which ECM:host mutualism may be affected. We evaluated how N fertilization altered host interactions and gene transcription between Eucalyptus grandis and Pisolithus microcarpus or Pisolithus albus, two closely related ECM species that typically co‐occur within the same ecosystem. Our investigation demonstrated species‐specific responses to elevated N: P. microcarpus maintained its ability to transport microbially sourced N to its host but had a reduced ability to penetrate into root tissues, while P. albus maintained its colonization ability but reduced delivery of N to its host. Transcriptomic analysis suggests that regulation of different suites of N‐transporters may be responsible for these species‐specific differences. In addition to N‐dependent responses, we were also able to define a conserved 'core' transcriptomic response of Eucalyptus grandis to mycorrhization that was independent of abiotic conditions. Our results demonstrate that even between closely related ECM species, responses to N fertilization can vary considerably, suggesting that a better understanding of the breadth and mechanisms of their responses is needed to support forest ecosystems into the future.